اسلامی نظام کے خلاف نرم بغاوت: فوجداری جرم قرار دینے کے امکانات اور ریاست کے کردار کا تنقیدی مطالعہ: Soft Rebellion Against the Islamic Order: Possibilities of Criminalization and a Critical Study of the Role of the State (Al-Qamar, 2025)
This study investigates the possibility of criminalizing the "soft subversion" of the Islamic political system and explores appropriate governmental responses to such activities. The research examines the conceptual and jurisprudential dimensions of soft subversion and proposes strategic mechanisms for addressing it within an Islamic legal framework. The theoretical section defines soft subversion as a deliberate and organized effort to undermine the Islamic system without resorting to physical violence. It is clearly differentiated from legitimate and constructive criticism. From a jurisprudential standpoint, the study concludes that if soft subversion poses a real and substantial threat to the integrity of the Islamic system, it can be classified under the category of muharaba (armed rebellion or war against the state). This is based on the apparent meaning of relevant Qur'anic verses, which do not necessarily require the use of weapons for the crime of muharaba. Any act that is socially recognized as equivalent to rebellion or corruption regardless of whether it involves physical force may be included in this category. Regarding criminal response, the study argues that if such subversive activities occur in non-violent forms such as online platforms, media campaigns, or cyberspace, the Islamic authority may impose punishments based on the principle of maslahah (public interest). However, in such cases where there is no actual bloodshed it recommends avoiding capital punishment and instead suggests penalties such as exile or imprisonment. The study underscores the critical importance of distinguishing between soft subversion and lawful dissent in the formulation of penal and judicial policies.
Keywords: Criminalization, Soft Subversion, Islamic Governance, Legitimate Criticism, Jurisprudence.